(untitled) (Research, Society and Development, 2021)
Research on The Completion Of Nursing Undergraduate Course inserted in the Line of Research Organization and Management of Health Services Care. The objective since the study was to identify the situations that contribute or hinder the practice of self-care of nursing undergraduates of a private university in Rio de Janeiro during the undergraduate period and in the experience of the SARS-CoV-2 pandemic. A descriptive and exploratory study was carried out, with a qualiquantitative approach in a Private Institution of Higher Education located in the North Zone of the City of Rio de Janeiro through semi-structured interviews through an online form. The results of closed questions, sociodemographic and socioeconomic profile were tabulated in percentage through microsoft excel software, 2010 and the open, qualitative questions were submitted to content analysis proposed by Bardim. The study included 116 nursing undergraduates with predominance in young adults, single, without children, from a family with nuclear education with an average family income of 1 to 3 minimum wages and who are dedicated to studies and work in concomitance. This research reached its objective by exposing the difficulties faced in the practice of self-care by nursing undergraduates during face-to-face graduation, evaluating how their worst factor is stress from the need to study in concomitance with work activity and in the evaluation of the practice of self-care during the pandemic with the virtualization of disciplines, the main stressing factor that hinders the practice of self-care is the sudden change in the routine of students.